2013
DOI: 10.1111/ajt.12275
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized Osteomyocutaneous Allografts Are Permissive to Tolerance by Induction-Based Immunomodulatory Therapy

Abstract: contributed equally to this study.Vascularized composite allografts (VCAs) are unique among transplanted organs in that they are composed of multiple tissues with disparate antigenic and immunologic properties. As the predominant indications for VCAs are non-life-threatening conditions, there is an immediate need to develop tolerance induction strategies and to elucidate the mechanisms of VCA rejection and tolerance using VCA-specific animal models. In this study, we explore the effects of in vitro induced don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…We show that sustained low-dose delivery of rapamycin by Rapa-ISFI could promote significantly higher levels of chimerism of both lymphoid and myeloid lineages at POD21. At this time, the levels of myeloid chimerism were elevated and positively correlated with graft survival, suggesting that initial high levels of donor granulocytes and monocytes may correlate with the engraftment of donor pluripotent hematopoietic stem cells (HSC) as recently demonstrated in mice receiving HSC transplantation after antibody-mediated clearance of recipient HSC 3032 . To support this hypothesis we performed bone marrow analysis demonstrating a the presence of a small number of donor-derived CD34 + and/or CD133 + cells residing in the recipient bone in all the non-rejecting rats from Groups 2, 3 and 4.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…We show that sustained low-dose delivery of rapamycin by Rapa-ISFI could promote significantly higher levels of chimerism of both lymphoid and myeloid lineages at POD21. At this time, the levels of myeloid chimerism were elevated and positively correlated with graft survival, suggesting that initial high levels of donor granulocytes and monocytes may correlate with the engraftment of donor pluripotent hematopoietic stem cells (HSC) as recently demonstrated in mice receiving HSC transplantation after antibody-mediated clearance of recipient HSC 3032 . To support this hypothesis we performed bone marrow analysis demonstrating a the presence of a small number of donor-derived CD34 + and/or CD133 + cells residing in the recipient bone in all the non-rejecting rats from Groups 2, 3 and 4.…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, our study clearly shows that low-dose rapamycin delivered by ISFI, induced T reg cells in the peripheral blood and in VCA-skin. The capacity of rapamycin to induce T reg alone or in combination with other treatments has been extensively reported 3032 . We demonstrated that the frequency of T reg in blood and VCA-skin correlated with the promotion of graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Recipients that were tolerant to VCA showed highest peripheral mixed chimerism at POD30. Degree of chimerism then gradually declined to the background level at POD90 [25]. The level of CD4 + FoxP3 + Tregs was significantly higher in recipients tolerant to VCA.…”
Section: Discussionmentioning
confidence: 96%
“…The central roles of the thymus and deletional tolerance mechanisms are well established in chimerism-based immunologic tolerance protocols. However, in addition, peripheral mechanisms dependent on Treg (CD4 + Foxp3 + cells) were reported to play a critical role in the immune responses to solid organ transplants (27), as well as VCA (40). In studies of BMT with CoB, thymic-independent early deletion and anergy of alloreactive CD4 + T cells in the peripheral lymphoid organs have been demonstrated, and both activation-induced cell death and passive cell death initially contribute to peripheral CD4 + T effector cell deletion, highlighting a critical phenomenon for tolerance induction (20,41).…”
Section: Discussionmentioning
confidence: 99%